어린이급식관리지원센터 지원에 대한 효과 평가: 메뉴관리 및 식사다양성 - 김혜영; 양일선; 채인숙; 이보숙; 박문경; 김하영; 강태석; 임동길; 이진하; 이해영; Kim, Hye-Young; Yang, Il-Sun; et al. (Korean journal of community nutrition, 2013)
The purpose of this study was to evaluate the effectiveness of Centers for Child-care Foodservice Management (CCFSM)'s support on menu management in child-care centers and kindergartens by comparing two perspectives of pre-support vs. post-support and established vs. non-established. To evaluate dietary variety, we used methods that considered both Dietary Diversity Score (DDS) and Dietary Variety Score (DVS). For surveying pre-support and post-support state by CCFSM, we collected and analyzed menus of June and September, 2012, targeting 7 CCFSM supported institutions. Meanwhile, for surveying state in CCFSM established and non-established areas, we collected and analyzed menus of June, 2012, which were implemented in institutions in CCFSM established (181 places) and non-established (106 places) areas. The results of evaluation on the dietary support by CCFSM showed that post-supporting state by CCFSM (95.3%) was significantly higher than pre-supporting state (77.2%) (p < 0.001) and established areas (87.4%) were significantly higher than non-established ones (77.2%) (p < 0.05) on 'Meeting the DRI for infant'. Evaluation of dietary variety between pre- and post-support state by CCFSM showed that post-support state (total 77.3 point) was higher than pre-support state (total 76.4 point). Evaluation of dietary variety between established and non-established areas showed that established areas (total 81.1 point) were significantly higher than non-established ones (total 77.1 point) (p < 0.001). Therefore, it is considered that dietary support service conducted by CCFSM contributes to improve variety level of diet provided by child-care centers and kindergartens.